2020
DOI: 10.1155/2020/8167038
|View full text |Cite
|
Sign up to set email alerts
|

Application of High‐Strength Lightweight Concrete in Gob‐Side Entry Retaining in Inclined Coal Seam

Abstract: Gob-side entry retaining (GSER) is a popular no-pillar mining technology that can increase coal recovery rate. We propose the application of high-strength lightweight (HSLW) concrete to construct the gob-side support body (GSSB) in NO. 411 inclined working face of Jingang Coal Mine. Firstly, the mechanical model of retained roadway was established, and the calculation for limit angle of GSSB stability and support resistance was mathematically derived. Using the performance test, the optimal proportion of LC50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Gob-side entry retention (GER), as an important technique in coal mining system without pillars [1][2][3][4], can improve the recovery rate of coal resources, reduce the rate of tunnelling of roadways, and avoid the waste of resources [5], owing to which it has been widely used in various coal mines in countries such as China, Germany, Poland, and the United Kingdom and has achieved remarkable economic and social benefits [6]. As a conventional material for roadway sidewall supporting, concrete blocks are characterised by large support resistance in the early stage, large rate of increase in resistance, favorable roof-cutting effect, and favorable sealing effect of the goaf.…”
Section: Introductionmentioning
confidence: 99%
“…Gob-side entry retention (GER), as an important technique in coal mining system without pillars [1][2][3][4], can improve the recovery rate of coal resources, reduce the rate of tunnelling of roadways, and avoid the waste of resources [5], owing to which it has been widely used in various coal mines in countries such as China, Germany, Poland, and the United Kingdom and has achieved remarkable economic and social benefits [6]. As a conventional material for roadway sidewall supporting, concrete blocks are characterised by large support resistance in the early stage, large rate of increase in resistance, favorable roof-cutting effect, and favorable sealing effect of the goaf.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, the control principle of roadways was proposed-reasonable selection of the width of the coal pillar, supported with a high strength and large elongation anchor, and using a pair of anchor cables and grouting to strengthen the narrow coal pillar [15][16][17][18]. Liu et al confirmed the determination of the reasonable width of the isolated coal pillar is the key to ensure safe mining in the deep coal seam with goaf, which is concluded as follows: (1) The evolution of the overburden space structure during mining in the goaf area is a "fixed S-type, mobile S-type, conjoined S-type, C-type, and U-type", and the stress evolution process of the isolated coal pillar is "fixed support pressure, mobile support pressure, stress superimposition, coal pillar stress concentration"; (2) Causes of goaf-induced rockburst induced by mining is that the stress of the coal body reaches the impact stress condition; (3) Under the condition of high-pressure relief around the isolated coal pillars, it was determined that the reasonable width of the isolated coal pillars was 65 m, and good results were obtained through practice [19][20][21]. Wang et al studied the deformation law and control technology of a goaf-side entry driving heading mining face, obtained that the surrounding rock exhibits asymmetric deformation, and that the narrow coal pillar and roof are severely deformed after being affected by the mining of adjacent mining faces, and put forward that improving the support strength of the narrow coal pillar and roof to form an effective bearing body is the key to maintaining the overall stability of the goaf-side entry driving heading mining face.…”
Section: Introductionmentioning
confidence: 99%